Effectiveness of The Implementation of Supreme Court Regulation Number 1 Year 2016 on Divorce Settlement - Marzuki Marzuki; Abidin Abidin; Hilal Malarangan (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC LAW AND SOCIETY, 2021)
The focus of this research is the effectiveness of implementing Supreme Court Regulation No. 1 of 2016 concerning the Mediation Process in the Court in the settlement of divorce cases at the Donggala’s Religious Court Class IB. The aim is to determine the implementation and effectiveness as well as the supporting and inhibiting factors for the implementation of the Supreme Court Regulation Number 1 of 2016 in the settlement of divorce cases. This research is a qualitative with a case study. The data were collected through observations, interviews, and documentation to the parties in the relevant research locations. The results of this study indicate that the Donggala Religious Court Class IB has implemented the practice of implementing mediation in accordance with the provisions of the Supreme Court Regulation Number 1 of 2016. However, the results of its implementation show that its effectiveness is still very small; this is evidenced by the high number of divorces each year. From the data on the number of divorces, it shows that divorce tends to increase which is dominated by divorce due to continuous disputes.